PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH TERHADAP HASIL BELAJAR SISWA SMA KELAS X - Yuli Tamar Filindity (Science Map Journal, 2022)
This study aims to determine the increase in learning outcomes of atomic structure concepts in class X Senior High School PGRI 2 Kairatu after applying the make a match type cooperative learning model. This study uses a quantitative descriptive research method. The sample in this study were students of class X MIA with a total of 25 students. Data collection techniques were carried out using test and non-test techniques. Based on the results of the study, it showed that 24 students (96%) reached the KKM and 1 student (5%) was in incomplete qualification. The increase in student learning outcomes is obtained from an average N-gain of 0.75 in the high category. From the research results, it can be concluded that the make a match type of cooperative learning model can improve the learning outcomes of students in class X Senior High School PGRI 2 Kairatu